Identifikasi Dampak Sanksi Ekonomi Terhadap Perekonomian Turki - Metasari Kartika; Irvan Sikajudin (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
This research aims to identify the economic sanctions obtained by the Turkish state and to know the data behaviour or trends in export data, imports, inflation, exchange rates and GDP before, during and after the provision of economic sanctions on the Turkish state. The study used secondary data from the presidential decree, newspaper, actual news, the official announcement which would later be processed into economic sanctions data, The World Bank, OECD, TÜIK, investing.com that some data was aggregated and processed by FRED. The study used the period before, on and after economic sanctions were granted to the Turkish state. After the data is collected, the analysis is then described in a descriptive and then illustrated through words and graphs, which will later use the techniques of deductive, inductive or mixed (deductive and inductive) and descriptive, that is collecting and compiling the necessary data in this study. The results of this study showed that economic sanctions in Turkey are present in various sectors and have a negative effect on affected sectors when economic sanctions are imposed against Turkey, So that if economic sanctions are not handled appropriately then this can make the Turkish economy continue to decline.